The Decent Work Impact in Enhancing Job Immersion/ An Applied Research in Labour and Vocational Training Directorate - Khaleel, Areej Saeed; huseen, Zahraa Abbas Ali (Journal of Economics and Administrative Sciences, 2022)
The research aims to identify decent work and its impact in enhancing job immersion. The questionnaire was adopted as a tool to analyze the sample responses of (81) workers to represent an estimated response rate of (88 per cent) out of the total population of (92) individuals. The research adopted descriptive-analytical approach, and reliability calculation, arithmetic means standard deviations, relative importance, and regression analysis adopted on SPSS v.25. The conclusion shows that there is a medium correlation between decent work and job immersion, and there is a low impact of decent work with its dimensions in job immersion; extract the most important acceptable components for job from the sample point of view about the open query of decent work. As well as practical implications highlighting the workers’ rights in Vocational Training Directorate in Iraq built on sound foundations that are guided by quality and acceptability by having decent work standards and enhancing job immersion. The research provides value, most notably interest to safe working conditions, and transfer of workers from a situation of worry to a stable situation by reducing the terms of the contract service period, and conversion of temporary contracts to permanent members